Utilization of vertebroplasty and kyphoplasty procedures throughout the United States over a recent decade: an analysis of the Nationwide Inpatient Sample - Laratta, Joseph L.; Shillingford, Jamal N.; Lombardi, Joseph M.; Mueller, John D.; Reddy, Hemant; Saifi, Comron; Fischer, Charla R.; Ludwig, Steven C.; Lenke, Lawrence G.; Lehman, Ronald A. (Journal of Spine Surgery; Vol 3, No 3 (September 29, 2017): Journal of Spine Surgery, 2017)
Background: Given the increasing societal focus on health care utilization and value-based care, it is essential to understand the demographic and economic data surrounding percutaneous vertebral augmentation procedures performed in the United States. Double-blinded prospective randomized controlled trials have shown no benefit to the use of vertebroplasty over a sham procedure in the treatment of vertebral fractures. Contrastingly, kyphoplasty may be beneficial when appropriately indicated. Methods: The National Inpatient Sample (NIS) database was queried for patients who underwent either kyphoplasty (ICD-9-CM 81.66) or vertebroplasty (ICD-9-CM 81.65) procedures between 2006 and 2014 across 44 states. Demographic and economic data were obtained which included the annual number of surgeries, age, sex, insurance type, location, and frequency of routine discharge. The NIS database represents a 20% sample of discharges from U.S. hospitals, which is weighted to provide national estimates. Results: In 2014, an estimated total number of 19,420 kyphoplasty and 6,130 vertebroplasty procedures were performed across the United States. The number of vertebroplasty procedures decreased 53% from 13,128 in 2008. Similarly, the number of kyphoplasty procedures decreased 17% from 23,320 in 2007. Based on payer, Medicare patients comprised 83% of those billed for kyphoplasty and vertebroplasty, and 75% of procedures were utilized in areas designated as “not low income”. In 2014, patients in the South Atlantic region comprised 24% of vertebroplasty and 28% of kyphoplasty cases, far more than any other region. Additionally, kyphoplasty and vertebroplasty were more often performed in teaching facilities rather than community hospitals (60% and 67%, respectively). Conclusions: Since the publication of two double-blind, prospective randomized controlled trials showed no benefit of vertebroplasty over a sham procedure, there has been a significant decrease in both kyphoplasty and vertebroplasty procedures.